Impelementasi Metode Tasmi Pada Progam Tahfidz Siswa SDUT Masyitoh Bandungrejo - Khikmah, Tiara Aulia; Alias’ad, Alias’ad (LP2M Universitas Islam Ahmad Dahlan, 2025)
This manuscript is a study aimed at analyzing the implementation of the Tasmi' method in the Qur'an memorization program at SDUT Masyitoh Bandungrejo. The Tasmi' method is one of the techniques used to improve students' ability to memorize the Qur'an. This research uses a qualitative method with data collection techniques including observation, interviews, and documentation. The results of the study show that the implementation of the Tasmi' method in the Qur'an memorization program at SDUT Masyitoh Bandungrejo has been running effectively. Teachers have applied the Tasmi' method efficiently to enhance their students' Qur'an memorization skills. In addition, the students have shown high motivation and interest in memorizing the Qur'an. This study concludes that the implementation of the Tasmi' method in the memorization program can significantly improve students’ Qur'an memorization abilities. Therefore, the Tasmi' method can be considered an effective method for teaching Qur'an memorization (Tahfidz).